Analysis of 2-methylthio-derivatives of isoprenoid cytokinins by liquid chromatography-tandem mass spectrometry - Tarkowski, Petr; Václavíková, Kateřina; Novák, Ondřej; Pertry, Ine; Hanuš, Jan; Whenham, Robert; Vereecke, Danny; Šebela, Marek; Strnad, Miroslav (Analytica chimica acta, 2010)
A sensitive and reliable high-performance liquid chromatographic method with tandem mass spectrometric detection has been developed and used for the determination of 2-methylthio-cytokinin derivatives produced by the phytopathogenic actinomycete Rhodococcus fascians. The cultivation medium containing secreted cytokinins was concentrated and subjected to a solid-phase extraction (C18 and ion-exchange). The purified samples were further separated and analyzed by HPLC-ESI-MS/MS. This allowed to achieve chromatographic resolution of six highly hydrophobic cytokinin species including 2-methylthio-isopentenyladenine, 2-methylthio-isopentenyladenosine, 2-methylthio-trans-zeatin and 2-methylthio-trans-zeatin riboside and their cis-isomers when a reversed-phase chromatographic column (C4) and a mobile phase consisting of acetonitrile and 20 mM ammonium formate, pH 5, were used. Quantification was performed by a standard isotope dilution method using a multiple-reaction monitoring (MRM) mode. In the MRM mode, limits of detection reached 20-30 fmol and linear ranges spanned four orders of magnitude. Recovery values were between 35% and 65% and the analytical accuracy between 95% and 149%. The proposed bioanalytical method, which takes advantage of effective chromatographic separation of six 2-methyltio-derivatives (including isomers of zeatin-type cytokinins) and sensitive mass spectrometric detection, may become useful for plant biologists studying the significance of these substances in plant-microbe interactions.
Keywords: Cytokinins; Molecular Structure; molekulární struktura; Terpenes; tandemová hmotnostní spektrometrie; Chromatography, Liquid; terpeny; chromatografie kapalinová; cytokininy; Tandem Mass Spectrometry